Does obesity create a relative sense of excess poverty? - Yuval Arbel; Yifat Arbel; Amichai Kerner; Miryam Kerner; Miryam Kerner (Frontiers Media S.A., 2024)
BackgroundThis study investigates the potential relationship between obesity and self-ranking of poverty, as a proxy for self-awareness and happiness. To the best of our knowledge, this issue has not been previously explored based on self-ranking of poverty when income is controlled.MethodOrdered Probit Regressions. We propose a new measure for the influence of western social values and norms associated with discrimination against obese women.ResultsBased on a follow-up survey after two years, findings demonstrate a drop in the projected probability of self-ranking as "not poor" with the BMI from 0.73 to 0.37 (females) - 0.48 (males) when the level of income is controlled. Similar outcomes are obtained when the independent variables are lagged and thus avoid endogeneity concerns. Finally, additional outcomes support the conclusion that the lagged BMI Granger-cause self-ranking of poverty for women, but not for men. Findings support the awareness of more obese women to lower prospects of finding a job.ConclusionSince according to twin studies, approximately 80% of obesity emanates from genetic factors, research findings stress the need to educate the public against prejudices on the grounds of obesity. In particular, our study seeks to evoke awareness among potential employers, which, in turn, might motivate avoidance of, or at least reduction in, an implicit wage penalty against obese women.